THE INFLUENCE OF SOCIAL SUPPORT ON WORK FAMILY CONFLICT IN FEMALE TEACHERS IN SLB BANJARMASIN - Fatoni, Irsyad (Jurnal Kajian Pendidikan dan Psikologi, 2023)
Study This aim is to know, influence, support, and socially against work-family conflict among female teachers in SLB Banjarmasin. Subject in study This owns a number of kiteria, namely female teachers who have already married or become teachers at school outside of ordinary (SLB) in Banjarmasin. Measurement done with the support social or work-family conflict  scale.Analysis of the data used is a simple linear regression test. Based on the results of the simple linear regression test, it was found that the mark significance is p < 0.05 (0.000 < 0.05), meaning that social influence is significant towards work-family conflict. Results in the study This can be concluded from the hypothesis in the study, which is proven to be significant, i.e., there is influence, support, and social-work-family conflict among female teachers at SLB Banjarmasin.